G365(P) Retrospective cohort study of (p)ior reversible encephalopathy syndrome (pres) in paediatric oncology patients over a 10 year period. (12th March 2018) - Wong-Spracklen, VMY; Messahel, B; Krishnakumar, D
Abstract : Aims: Literature regarding (P)ior reversible encephalopathy syndrome (PRES) in paediatric oncology is limited. Clinical symptoms of PRES include seizures, headaches, altered consciousness, and visual disturbances. We describe the seizures in PRES, outcomes and need for anti-epileptic medication of this clinical syndrome. Methods: A retrospective cohort study using data from the East Anglia paediatric oncology database for suspected adverse events (SAE) from chemotherapy was conducted. Oncology patients aged 16 and below, from 1 January 2007 until 15 June 2017 who had developed seizures while undergoing chemotherapy, were included. We identified the chemotherapy administered before onset of seizures, magnetic resonance imaging (MRI) reports, and patient outcomes based on anti-epileptic drugs (AED) requirement at 6, 12, 24 months or more after seizure occurrence. Results: 38/420 (9.0%) paediatric patients undergoing chemotherapy developed seizures. 14/38 (36.8%) were confirmed to have had PRES. The mean age for PRES-associated seizures was 10.1 years (±SD 3.7 years). The mean interval between administration of chemotherapy and onset of seizures in PRES was 7 days±SD 5 days (Median 5 days, range 1–17 days). Chemotherapy agents associated with seizure occurrence in PRES were methotrexate in 10/14 (71.4%), ifosfamide in 3/14 (21.4%) and vincristine 1/14 (7.1%). High signal abnormalities seen on MRI changes due to PRES was seen in occipital-parietal lobe (43%), frontal lobe (43%), centrum semiovale (14%), caudate nucleus (14%), deep white matter (14%) and temporal lobe (7%). Only 1/14 (7%) of PRES patients remained on AED for 11 months, compared to 3/24 (12%) of non-PRES patients who remained on AED at 5 years follow-up. Conclusion: PRES is an important differential to consider in paediatric oncology population developing seizures. The chemotherapeutic agents associated with PRES are often Methotrexate, Vincristine and Ifosfamide. The outcome for seizures associated with PRES is good as only 7% require anti-epileptic medication for the first 11 months post-PRES. Further studies should be carried out in identifying prognostic markers, e.g. blood pressure, which may aid early identification of patients at risk of PRES and who may benefit from proactive preventative measures.